2022
DOI: 10.1186/s12935-022-02603-0
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell leukemia-1 expression in cancers of the oral cavity: a scoping review

Abstract: Background B cell lymphoma-2 (Bcl-2) family members play important roles in cell survival as well as cell death. The role of myeloid cell leukemia-1 (Mcl-1), an important member of the Bcl-2 family, is well established in hematopoietic malignancies. However, the association between Mcl-1 and oral cavity, cancers is not clearly defined. Methods A scoping review was conducted until June 30, 2021, using four major databases, PubMed, Scopus, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…Mcl-1, a member of the Bcl-2 family with antiapoptotic properties, promotes cell survival by inhibiting apoptosis (20). Our group has previously shown that Mcl-1 is overexpressed in oral cancer and is closely associated with poor clinical outcomes, suggesting that the inhibition of Mcl-1 might be a good strategy for the treatment of oral cancer (21,22). Mcl-1 regulates mitochondrial outer membrane permeabilization, which is a vital process in the initiation of apoptosis, by engaging the interaction with BH3-only proteins, such as Bim, and t-Bid.…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1, a member of the Bcl-2 family with antiapoptotic properties, promotes cell survival by inhibiting apoptosis (20). Our group has previously shown that Mcl-1 is overexpressed in oral cancer and is closely associated with poor clinical outcomes, suggesting that the inhibition of Mcl-1 might be a good strategy for the treatment of oral cancer (21,22). Mcl-1 regulates mitochondrial outer membrane permeabilization, which is a vital process in the initiation of apoptosis, by engaging the interaction with BH3-only proteins, such as Bim, and t-Bid.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the potent anticancer mechanism of action of PPT in OSCC, apoptosis associated with the Bcl-2 family of proteins, particularly myeloid cell leukemia-1 (Mcl-1) was assessed. In OSCC, the Mcl-1 gene is commonly amplified and upregulated, which affects the clinical course and survival of patients with this disease (21)(22)(23)(24). Mcl-1 is also upregulated and is associated with poor outcomes in other malignant tumors, such as hematologic malignancies (25), breast cancer (26,27), lung (28), and gastric cancer (29).…”
Section: Introductionmentioning
confidence: 99%
“…Mcl-1 blocks the oligomerization of the pro-apoptotic Bcl-2 family members, Bax and Bak, which sequesters them to produce protein-permeable holes in the mitochondrial outer membrane ( 30 - 32 ). Finally, a reduction in Mcl-1 expression promotes cytochrome C release into the cytoplasm, which activates the caspase cascade and induces apoptosis ( 21 ). Based on these findings, targeting Mcl-1 may represent a promising approach for treating OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the potent anticancer mechanism of action of PPT in OSCC, we examined apoptosis associated with the Bcl-2 family, particularly myeloid cell leukemia-1 (Mcl-1). In OSCC, the Mcl-1 gene is commonly ampli ed and upregulated, which affects the clinical course and patient survival [20][21][22][23].…”
mentioning
confidence: 99%
“…Bak and Bax, two pro-apoptotic members of the Bcl-2 family, are prevented from oligomerizing by Mcl-1 which sequesters them to produce protein-permeable holes in the mitochondrial outer membrane [29][30][31]. Finally, a reduction in Mcl-1 expression promotes cytochrome c release into the cytosol, which activates the caspase cascade and induces apoptosis [20]. Based on these ndings, targeting Mcl-1 may represent a promising approach for treating OSCC.…”
mentioning
confidence: 99%